Development and Validation of Discriminative Dissolution Test for Tenofovir Disoproxil Fumarate Formulation - Gupta, Krishna; Ukey, Anjali; Umap, Arpita; Umekar, Milind (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives and Introduction This study uses HPLC and UV spectrophotometric methods to develop and validate a differential dissolution test method for quality control of tenofovir disoproxil fumarate in a tablet. Tenofovir disoproxil fumarate is a medicine used in combination therapy to treat HIV infection. It has antiviral, prodrug, and HIV-1 reverse transcriptase inhibitory properties. Materials and Methods Phosphate buffer 6.8, water, and 0.01 N HCl were the components of the separation solution. The USP Apparatus II blade should be used at 75 rpm and 900 mL of 0.01 N HCl at 37º±0.5ºC for the best dissolving. Tenofovir disoproxil fumarate's in vitro release profiles perform well under these circumstances. This was done on Agilent ZORBAX C8 a 6x150 mm column, the temperature of the column was ambient, its flow rate was 1.0 mL/min and the detection wavelength was 260 nm. The mobile phase comprised of 70:30 v/v mixture of methanol and formic acid solution. When the conditions were optimal, this approach demonstrated good release. Method validation was carried out as per the ICH guidelines. The drug follows zero-order release kinetics. Results When the conditions were optimal, this approach demonstrated good release. Method validation was carried out as per the ICH guidelines. The drug follows zero-order release kinetics. Conclusion The results obtained by the proposed method for dissolution test for Tenofovir disoproxil fumarate tablet formulation were found to be reliable, rugged, linear, accurate and precise.
Keywords: Discriminative dissolution; Dissolution test; HPLC; Tenofovir disoproxil fumarate.